Psychological Issues in Inflammatory Bowel Disease: An Overview. (21st June 2012) - Sajadinejad, M. S.; Asgari, K.; Molavi, H.; Kalantari, M.; Adibi, P.
Abstract : Inflammatory bowel disease (IBD) including Crohn's disease (CD) and ulcerative colitis (UC) is a chronic and disabling disease with unknown etiology. There have been some controversies regarding the role of psychological factors in the course of IBD. The purpose of this paper is to review that role. First the evidence on role of stress is reviewed focusing on perceived stress and patients' beliefs about it in triggering or exacerbating the course of IBD. The possible mechanisms by which stress could be translated into IBD symptoms, including changes in motor, sensory and secretory gastrointestinal function, increase intestinal permeability, and changes in the immune system are, then reviewed. The role of patients' concerns about psychological distress and their adjustment to disease, poor coping strategies, and some personality traits that are commonly associated with these diseases are introduced. The prevalence rate, the timing of onset, and the impact of anxiety and depression on health-related quality of life are then reviewed. Finally issues about illness behavior and the necessity of integrating psychological interventions with conventional treatment protocols are explained.